A Mesh Sensor Network based on Bluetooh: Comparing Topologies to Crop Monitoring - Alves, Luan; Antunes, Elida; Ferreira, Ricardo; Augusto Nacif, José (Anais Estendidos do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2019)
The growth of the world population increases the demand for food and other products from agriculture. Therefore, it is increasingly needed to enhance and optimize the productivity of farms. Through using a Wireless Sensor Network (WSN) and the application of the internet of things (IoT) technologies, we can better monitor the condition of farm crops. In this work, we designed a Bluetooth Low Energy mesh network joined fluorescence sensors for agricultural crop monitoring, and also we evaluated the suitability of this solution in a crop field scenario.